Development and implementation of an “Internet ” integrated service model for antepartum, intrapartum, and postpartum care in maternal and child specialty hospitals: A randomized controlled trial - Chen Shaochuan; He Lianci; Zhang Qiongyue; Wang Xin; Xie Huiqiong; Tan Ying; Feng Xiaohui; Li Huimin (Digital Health)
Objective This study investigates the effects of developing and implementing an integrated service model for antepartum, intrapartum, and postpartum care in maternal and child specialty hospitals under the deep integration of Internet technology. The goal is to provide practical references for addressing declining birth rate challenges and promoting the sustainable development of maternal and child specialty hospitals. Methods Using a convenience sampling method, 100 pregnant and postpartum women from a tertiary maternal and child health hospital in Chengdu, China, were selected as the participants for this study. A random number table was used to assign the participants into the control group and the intervention group, with 50 participants in each group. The control group received conventional nursing care, while the intervention group was provided with an integrated service model for antepartum, intrapartum, and postpartum care, fully implemented with Internet technology. A comprehensive comparative analysis was conducted between the two groups across several key dimensions, including the number of return visits within 42 days postpartum: The actual number of return visits for checkups, treatments, or consultations due to various health issues during this period was recorded and compared; Postpartum complications within 42 days: The occurrence rates of common complications, such as postpartum infections, hemorrhage, and milk stasis, were meticulously documented and analyzed for both groups. Service satisfaction: A nursing satisfaction questionnaire was used to objectively and comprehensively assess the satisfaction levels of participants in both groups with the care they received. Willingness for postpartum follow-up visits: Differences in participants’ subjective willingness and proactive attitudes toward arranging subsequent postpartum visits were thoroughly examined. Psychological indicators: Using psychological assessment scales, the psychological status of the two groups was evaluated from the establishment of personal health records to postpartum follow-up, analyzing the psychological differences between the two groups. Results Through systematic data collection, organization, and rigorous statistical analysis, the results revealed that the average number of return visits within 42 days postpartum was significantly lower in the intervention group (0.16 ± 0.42) compared to the control group (1.44 ± 1.11) ( t  = −7.630, P  < .001). For service satisfaction, 84.00% (42/50) of participants in the intervention group were very satisfied, significantly higher than 52.00% (26/50) in the control group (χ² = 3.170, P  = .001). The incidence of mastitis within 42 days postpartum was 2.00% (1/50) in the intervention group, markedly lower than 28.00% (14/50) in the control group (χ² = 2.670, P  < .001). For willingness to seek follow-up visit, 96.00% (48/50) of participants in the intervention group stated they would return to the hospital if they had health issues, compared to 82.00% (41/50) in the control group (χ² = 5.010, P  = .025). 92.00% (46/50) of participants in the intervention group were willing to choose our hospital for the newborn's health checkup, significantly higher than 76.00% (38/50) in the control group (χ² = 61.060, P  < .001). The 28 weeks GAD-7 scored lower in the intervention group (4.14 ± 0.73) than in the control group (5.27 ± 1.00) ( t  = −6.430, P  < .001) and also lower in the intervention group than in the control group at admission (5.58 ± 1.40 vs. 7.29 ± 1.61; t  = −5.630, P  < .001). There was no significant difference in 28 weeks EPDS scores between two groups (9.02 ± 0.68 vs. 9.18 ± 0.78; t  = −1.110, P  = .270). The intervention group showed significantly lower EPDS scores at 42 days postpartum (7.84 ± 0.71 vs. 9.61 ± 1.84; t  = −6.310, P  < .001). Conclusion The integrated service model for antepartum, intrapartum, and postpartum care in maternal and child specialty hospitals, based on the “Internet+” concept, effectively integrates Internet technology with critical processes in nursing services. This model precisely and efficiently addresses pregnant and postpartum women's unique maternal and childcare needs at different physiological stages. It demonstrates significant advantages in optimizing medical resource allocation, improving the quality and efficiency of nursing services, and enhancing patients’ healthcare experiences and trust. The findings of this empirical study provide robust evidence for the model's effectiveness in nursing care. The successful implementation of this innovative service model offers new perspectives and directions for transforming and upgrading maternal and child specialty hospitals in the face of declining birth rates and the associated challenges and opportunities. It holds significant value for broader application and promotion, with promising prospects for further development.